1988
DOI: 10.1111/j.1600-0528.1988.tb00574.x
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year oral health dose‐response study of sodium monofluoro‐phosphate dentifrices with and without zinc citrate: anti‐caries results

Abstract: A 3-yr clinical trial has been conducted on 3000 12-yr-old children in Lanarkshire, Scotland, with the aim of investigating the effects on oral health of toothpastes containing both sodium monofluorophosphate and zinc citrate, the former being present at fluoride levels of 1000, 1500, and 2500 ppm F. No significant difference in caries increments was found between the group of children using toothpastes incorporating zinc citrate and their counterparts using zinc-free pastes. However, a significant anti-caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 11 publications
4
70
0
5
Order By: Relevance
“…Some clinical studies have shown that with 1000 to 2500 ppm F toothpaste an increase of 6% is obtained in dental caries protection for each 500 ppm (23,35).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have shown that with 1000 to 2500 ppm F toothpaste an increase of 6% is obtained in dental caries protection for each 500 ppm (23,35).…”
Section: Discussionmentioning
confidence: 99%
“…Data from in vitro and in situ studies support this proposition [19,20]. Overall, the effect of zinc on caries development is proposed to be neutral [6,21].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Clinical trials indicate that within the range 1,000 to 2,500 ppm F an increase in fluoride of around 500 ppm results in an additional 6% reduction in dental caries. 17,18 In the UK 41% of the parents of young children aged 1fi to 2fi years claim to use a toothpaste containing less than 600 ppm F. 10 Toothpastes containing higher concentrations of fluoride confer greater protection against dental caries but increase the risk of fluorosis. In contrast, low fluoride toothpastes provide less protection against dental caries but reduce the risk of fluorosis.…”
Section: Discussionmentioning
confidence: 99%